2019
DOI: 10.1007/s12144-019-00444-1
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia, Literacy Difficulties and the Self-Perceptions of Children and Young People: a Systematic Review

Abstract: This systematic review investigates the links between literacy difficulties, dyslexia and the self-perceptions of children and young people (CYP). It builds on and updates Burden's (2008) review and explores how the additional factors of attributional style and the dyslexia label may contribute to CYP's self-perceptions. Nineteen papers are included and quality assessed. Quantitative papers measured the self-reported self-perceptions of CYP with literacy difficulties and/or dyslexia (LitD/D) and compared these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 50 publications
(129 reference statements)
5
44
0
5
Order By: Relevance
“…Gunnel Ingesson (2007) found that dyslexia had a large effect on more than 70% of young people's academic outcomes; they had chosen non-academic pathways, rather focussing on practical routes. This echoes conclusions drawn by Gibby-Leversuch et al (2019); many studies found that those with dyslexia tended to view themselves poorly academically, even when their attainment was in line with their peers. Thus, where individuals have dyslexia it is likely that their position in their social network is influenced by it, through their own self-concept and by their relationships with others.…”
Section: Relationships Through Dyslexiasupporting
confidence: 79%
See 1 more Smart Citation
“…Gunnel Ingesson (2007) found that dyslexia had a large effect on more than 70% of young people's academic outcomes; they had chosen non-academic pathways, rather focussing on practical routes. This echoes conclusions drawn by Gibby-Leversuch et al (2019); many studies found that those with dyslexia tended to view themselves poorly academically, even when their attainment was in line with their peers. Thus, where individuals have dyslexia it is likely that their position in their social network is influenced by it, through their own self-concept and by their relationships with others.…”
Section: Relationships Through Dyslexiasupporting
confidence: 79%
“…However, they did report that many young people had been bullied due to their difficulties with literacy, which had in turn negatively affected their self-esteem. However, Gibby-Leversuch et al (2019) report that young people's relationships were influenced both positively and negatively by their dyslexia. Particularly influential within relationships was how young people conceptualise their own dyslexia.…”
Section: Relationships Through Dyslexiamentioning
confidence: 96%
“…Taking into account the target group and main difficulties -our concept -the age group starts from 16. This is a very complicated age in general (Giles, 2005a;2005b); sometimes there are identity formation problems (Giles, 2005b); sometimes -unique mental health crisis (Giles, 2005a); and especially for those who have dyslexia (Gibby-Leversuch, Hartwell & Wright, 2019;Eden et al, 2004). Some of these individuals have had a really good support system in school during the first years of education.…”
Section: Theoretical Framework and Findings In Scientific Literaturementioning
confidence: 99%
“…Indeed, in his seminal article on the vicious circle he termed the Matthew Effect, Stanovich (1986) observed "Initial and specific difficulties in learning to read may result in generalized deficits in learning because of the behavioral-cognitive-motivational spinoffs from failure at such crucial tasks as learning to read" (p. 389). Unfortunately, despite early work (Geisthardt and Munsch, 1996;Alexander-Passe, 2006;Burden, 2008) there has been no systematic analysis of mental health issues in dyslexic children, though recent studies and reviews indicate that dyslexic adolescents do suffer from internalizing problems (anxiety and depression) but not necessarily lower self esteem (Boyes et al, 2018(Boyes et al, , 2020Eyre et al, 2019;Gibby-Leversuch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%